BEYOND THE COVER: MARKETEERS MAGAZINE'S DIGITAL ADAPTATION THROUGH COMMODIFICATION - Afandi, Ilham Akbar (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2024)
This research was motivated by the increasing number of online media that make it easier for people to access information quickly, causing a decrease in public interest in print journalism. As a result, many print media companies had to close. Marketeers magazine overcame this problem by making covers one of the primary weapons to attract public attention. Through this structural study, researchers analyzed how Marketeers magazine responded to these conditions with commodification made to content, readers, and workers. This research uses a critical model with a qualitative approach. This research method is a descriptive analysis and data collection method using in-depth interviews so that researchers can dig for more data and facts on critical informants and informants. The results of observations made with these interviews are compared between the results of interviews. The results found that Maketeers carried out a process of commodification of content, readers, and workers. From the commodification process, Marketeers magazine experienced an increase in sales. This can be a benchmark for print media industry entrepreneurs in Indonesia so that they can continue to exist in the Indonesian print media industry.